Factors associated with patient and health system delay in diagnosis and commencement of treatment for pulmonary tuberculosis in the Middle East and North Africa (MENA): systematic review - Eltayeb, Dalya (Department of Public Health and Family Medicine, 2016)
This MPH dissertation undertakes a systematic review on factors associated with patient and health system delay in diagnosing and commencing treatment for pulmonary tuberculosis in Middle East and North Africa (MENA). The dissertation is composed of three main parts: namely parts A, B and C. Part A is the research protocol, which give brief background to research topic and the process of this review. This systematic review aims to assess factors associated with patient and health system delay for diagnosis and initiation of treatment of pulmonary tuberculosis in Middle East and North Africa (MENA). Part B elaborates on the background and highlights the importance of this research by examining the existing theoretical and empirical literature relevant to the topic. Part C presents the entire research project in a format suitable for PLOS journal submission. The background of this research project is summarized and the results are presented and discussed.